2020
DOI: 10.1038/s41598-020-58691-3
|View full text |Cite
|
Sign up to set email alerts
|

A Spanish case-control study in <5 year-old children reveals the lack of association between MLB and VA astrovirus and diarrhea

Abstract: Novel human astroviruses (HAstV) were discovered 10 years ago and have been associated with fatal cases of central nervous system infections. Their role in gastroenteritis is controversial, as they have been identified in symptomatic and asymptomatic subjects. The aim of the study was to investigate novel HAstV in a gastroenteritis case-control study including a pediatric population in Spain over a one-year period. We included stool samples from patients with gastroenteritis and negative results for viruses sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The virus detection rates are supported by studies from other developed countries, such as Denmark, Spain and the USA. [26][27][28] Norovirus was the most prevalent of the studied viruses in the whole cohort but also in both subgroups. The norovirus detection rate of 7.2% in the asymptomatic is similar to previous publications.…”
Section: Discussionmentioning
confidence: 89%
“…The virus detection rates are supported by studies from other developed countries, such as Denmark, Spain and the USA. [26][27][28] Norovirus was the most prevalent of the studied viruses in the whole cohort but also in both subgroups. The norovirus detection rate of 7.2% in the asymptomatic is similar to previous publications.…”
Section: Discussionmentioning
confidence: 89%
“…HAstV MLB2 was identified a decade ago [51], and since then, it has been demonstrated that it is circulating in every continent [50]. In addition, it is associated with systemic and central nervous system infections [7,52] and has been identified in stool samples of asymptomatic children [53]. In our mNGS study, classic HAstV was found in plasma samples of a patient with digestive GvHD shortly before death, and HAstV MLB2 was found at low VL in plasma samples of a patient with diarrhea due to digestive GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to age Pediatr et al, (2019) showed that the co-infection between Astrovirus and other enter viruses is most common under 2 years [37], while Mozhgani et al, (2012) in Iran [38], Vu et al, (2020) in Spain, proved that the vast majority of children had co-infection with human astrovirus while they were one year old and under [39 ]. This may be related to the reality that in the lower age groups, infection of human astrovirus, and Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%